2003
DOI: 10.1073/pnas.0730639100
|View full text |Cite
|
Sign up to set email alerts
|

Male-biased transmission of deleterious mutations to the progeny in Arabidopsis thaliana

Abstract: The extent and cause of male-biased mutation rates, the higher number of mutations in sperm than in eggs, is currently an active and controversial subject. Recent evidence indicates that this male (sperm) bias not only occurs in animals but also in plants. The higher mutation rate in plant sperm was inferred from rates of evolution of neutral DNA regions, and the results were confined to the mitochondria and chloroplasts of gymnosperms. However, the relative transmission rates of deleterious mutations, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Notably, in many species, male cells transmit more mutations than the female to the offspring due to more germ cell divisions (Li et al, 2002;Whittle and Johnston, 2003). We further hypothesize that male-biased expression of new genes and male-biased mutation may be driven by the same evolutionary forces: male gametophyte competition ( Figure 6).…”
Section: Discussionmentioning
confidence: 95%
“…Notably, in many species, male cells transmit more mutations than the female to the offspring due to more germ cell divisions (Li et al, 2002;Whittle and Johnston, 2003). We further hypothesize that male-biased expression of new genes and male-biased mutation may be driven by the same evolutionary forces: male gametophyte competition ( Figure 6).…”
Section: Discussionmentioning
confidence: 95%
“…A largely unstudied biological system where gender-specific gene expression could significantly alter codon usage is plants. Recent findings, in A. thaliana , have indicated that male gametes pass on a greater number of induced harmful mutations to their offspring, suggesting that mutations are subject to less selection in male tissues/gametes than in female tissues/gametes [7]. Such findings at the population level (short-term), suggest that gender could also impact the selective processes that alter molecular evolution in plants, including the usage of synonymous codons.…”
Section: Introductionmentioning
confidence: 97%
“…Higher rates of mutation in the male germline, relative to the female germline, have been found in primates (Makova and Li 2002;Shimmin et al 1993), rodents (Chang et al 1994), cats (Pecon Slattery and O'Brien 1998), birds (Ellegren and Fridolfsson 1997), fish (Ellegren and Fridolfsson 2003), Arabidopsis (Whittle and Johnston 2003) and gymnosperms (Whittle and Johnston 2002). The primary explanation for the observed male-biased mutation rate is that DNA replication is mutagenic and that the average sperm contributing to each generation will have gone through more cell divisions than the average egg (Miyata et al 1987).…”
mentioning
confidence: 99%
“…Furthermore, this explanation is not sufficient to explain male-biased mutation for classes of mutation that are likely independent of DNA replication. For example, a male bias has been observed in Arabidopsis for the transmission of mutations that arise from UV irradiation (Whittle and Johnston 2003). Secondly, a weak male-biased mutation rate has also been found at primate CpG sites where mutations typically result from replication independent deamination of methylated cytosines (Taylor et al 2006).…”
mentioning
confidence: 99%